ACCOUNTING STANDARDS FOR MICRO, SMALL AND MEDIUM ENTERPRISES: EFFECTIVE OR NOT? - Nurmadi, Ruswan; Novietta, Liza (Accounting and Business Journal; Vol 2 No 2 (2020): ACCOUNTING AND BUSINESS JOURNALDO - 10.54248/abj.v2i2.1020, 2020)
Micro, Small and Medium Enterprises (MSMEs) in economies around the world are very large. It's easy to start a business because the capital needed is not as big as if you are doing a big business, making the number of micro, small and medium entrepreneurs increase every year. Micro, small and medium entrepreneurs have proven their ability to survive in the midst of a financial crisis. Still, there are fundamental problems faced, namely how can the business survive, develop or even excel in competition? Meanwhile, one of the requirements of a capital borrower such as banking is that the business must have financial reports in accordance with financial accounting standards set by regulators.  This study uses a literature review to see whether the Financial Accounting Standards for Micro, Small and Medium Enterprises are effective enough based on existing phenomena.